Zagadnienia Nośności Granicznej Elementów Rozciąganych i Zginanych w Zastosowaniu do Teorii Zbiorników Prostokątnych - Sawczuk, Antoni (Engineering Transactions, 1955)
This paper concerns the problems of the limit loads of elements subjected to simultaneous bending and tension. Structures made from two materials, brittle and ductile, are considered, the brittle material being subjected to compression and the ductile one to tension on the same way as W. Olszak had considered the limit analysis of bending plates, [10], [11] and [12]. An investigation of the limit state of such an element permits to observe that if tensile forces (the membrane state) are taken into consideration, a change of the index of orthotropy of the structure occurs resuting in the SO called «forced» orthotropy. At the same time the phenomenon of change of the homogeneous structure of the element into a heterogeneous one can occur, depending on the form of the function determining the distribution of tensile forces on the periphery of the plate. This heterogeneity is strictly determined for the given conditions of load and the given parameters determining the structure of the considered element. Considering the action of the tensile forces, the problem of knot forces for heterogeneous system is investigated in a way similar to that of K. W. Johansen for homogeneous plates subjected to bending. After the explanation of the theoretical problems concerning limit load of elements subjected to tension and bending, limit states of two rectangular tanks are considered on the basis of existing solutions for plates subjected to bending.